UPAYA DOMESTIKASI TANGKASI(Tarsius spectrum) MELALUI OPTIMALISASI PEMBERIAN PAKAN SECARA GRADUAL DAL AM PENANGKARAN - Kiroh, Hengki J (Research Center for Biology-Indonesian Institute of Sciences, 2009)
This research was conducted to change natural feeding behavior of Tarsius (Tarsius spectrum) using fresh life insect into fresh meal material as new introducing feeding material by gradually optimal feeding system in wire netting pen.This research was focused on preference of Tarsius into fresh meal as new introducing feeding material and nutrient consumption.Result showed that Tarsius was able to be interested in different fresh meal as new introducing feeding material within relatively short time and to be adaptable on different nutrient consumption. Therefore, it can be concluded that (1) domesticating process of Tarsius was able to change their natural feeding behavior using fresh life insects into fresh meal material as new introducing feeding within 27 day; (2) Average nutrient consumption of Tarsius for new introducing feeding varied one to each other in wire netting pen.